Self-Rated Benefits of Auditory Performance after Bonebridge Implantation in Patients with Conductive or Mixed Hearing Loss, or Single-Sided Deafness - Anna Ratuszniak; Piotr H. Skarzynski; Elżbieta Gos; Henryk Skarzynski (Life, 2022)
The Bonebridge implant can be a satisfactory solution for patients with conductive or mixed hearing loss (CHL or MHL), or with single-sided deafness (SSD). The aim of the study was to assess patients’ self-reported benefits with the Bonebridge and characterize the relationships between pre-implantation audiometric data, auditory functioning, and satisfaction after implantation. A focus was to see whether different types of hearing loss were associated with particular benefits. The study sample consisted of 81 patients. Procedures comprised pure tone audiometry before implantation, the Abbreviated Profile of Hearing Aid Benefit (APHAB) questionnaire, and a structured interview asking about satisfaction. Statistically significant improvements after implantation were found in all groups (CHL, MHL, SSD) on the APHAB questionnaire. In the structured interview, patients with SSD were the least satisfied. No significant correlation was found between pre-operative air-bone gap and bone conduction thresholds or with APHAB score. Bonebridge implantation is beneficial to patients with CHL or MHL, or with SSD. Assessment of patients for Bonebridge implantation is complex, and audiometric data should be complemented by patient-reported outcomes to provide deeper insight into their individual needs and attitudes.